Fragmentomic cfDNA Patterns in Noninvasive Prenatal Testing and Beyond - Kavish Kohabir; Rob Wolthuis; Erik A. Sistermans (Faculty of Medicine, Diponegoro University, 2021)
The release of fetoplacental cell-free DNA (cfDNA) into the maternal bloodstream opened up new avenues towards noninvasive prenatal testing (NIPT) for aneuploidies, hereditary DNA mutations and other pregnancy-related developmental disorders. Increasingly, cfDNA catches interest for its noninvasive screening value in other areas as well, including oncology. Although there are indications that cfDNA fragmentation is a non-random process, the etiology and different structural aspects of cfDNA are still not well known. The emerging field of cfDNA fragmentomics investigates the existence of tissue and disease specific cfDNA signatures and the chemistry and biology underlying the fragmentation process. This review sheds light on recent developments in cfDNA fragmentomics and illustrates their significance in NIPT improvement and beyond.We discuss aspects of fragment size distributions, epigenetic correlations and putatively enriched cfDNA fragment-end compositions. Combinatorial fragmentomic efforts have provided more insights into the roles of different enzymes that contribute to the fragmentation process in the tissue of origin and in the bloodstream. Altogether, these studies revealed multiple fragmentomic-related biomarkers that can be used to make noninvasive screening and other types of clinical use of cfDNA more robust, by raising its distinctive capacities. This includes multiple complementary approaches to determine the fetal fraction, a key determinant in NIPT. Furthermore, these developments translate to a better understanding of the encountered cfDNA patterns and will catalyze the expansion of screening possibilities in NIPT and beyond